2016
DOI: 10.1136/tobaccocontrol-2016-053188
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in tobacco retailer sales to minors by neighbourhood racial/ethnic composition, poverty and segregation, USA, 2015

Abstract: Objective Tobacco retailers are an important source of tobacco products for minors. Previous research shows racial discrimination in sales to minors, but no national study has examined neighborhood correlates of retailer underage sales. Methods We accessed publicly available results of 2015 FDA inspections of tobacco retailers (n=108,614). In this cross-sectional study, we used multilevel logistic regression to predict the likelihood of retailer sale to a minor based on tract characteristics. We assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…The current study showed that vape shop federal and state policy compliance in California was greater in neighbourhoods with higher proportions of white residents, consistent with the findings in other types of tobacco retailer shops (eg, tobacco shops, non-franchised shops, convenience stores) that sold combustible tobacco products. [12][13][14] While vape shops claim to offer a means of harm reduction, in contrast to the tobacco industry, 23 their patterns of non-compliance suggest that they may be exacerbating health disparities by exposing minority communities to greater risk. The presence of legal age signage was a notable finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed that vape shop federal and state policy compliance in California was greater in neighbourhoods with higher proportions of white residents, consistent with the findings in other types of tobacco retailer shops (eg, tobacco shops, non-franchised shops, convenience stores) that sold combustible tobacco products. [12][13][14] While vape shops claim to offer a means of harm reduction, in contrast to the tobacco industry, 23 their patterns of non-compliance suggest that they may be exacerbating health disparities by exposing minority communities to greater risk. The presence of legal age signage was a notable finding.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similar studies involving FDA inspection data across the USA have also shown that underage sales of tobacco were positively related to the proportion of residents with black and Latino ethnicities, adjusting for other neighbourhood variables. 13 Point-of-sale tobacco marketing is more prevalent in rural areas and in neighbourhoods with lower income and more black residents. 14 Recent studies on tobacco and vape shops in Colorado, 15 California, 16 Illinois, New York and Florida 17 documented violation of vape products sales to minors comparable to that of the combustible cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should also assess other subgroup differences in e-cigarette use, such as socioeconomic status (SES) and racial/ethnic and sexual minority groups. These subgroups have been traditionally targeted by the tobacco industry [5961]. …”
Section: Discussionmentioning
confidence: 99%
“…The geographical separation of individuals on the basis of race/ethnicity and SES is a fundamental cause for the tobacco industry's targeted marketing to demographic groups (i.e., African Americans, low-income individuals) most severely impacted by combustible tobacco use ( Yerger et al, 2007 ). To inform FDA cigar regulations, surveillance of retail marketing for LCCs in neighborhoods that have been racially targeted by tobacco marketing ( Lee, Landrine, Torres, & Gregory, 2016 ) is warranted. Specifically, we examined LCC availability, advertising, price promotions, and product placement overall, by store type, and racial/ethnic neighborhoods (Black/African American, Hispanic/Latino, Korean American, and non-Hispanic White).…”
Section: Introductionmentioning
confidence: 99%